Integrating Environmental Sustainability and Economic Efficiency (MMIT Proceedings, 2026)
This article examines the issues of integrating the principles of environmental sustainability and economic efficiency within the context of the modern economic development of Uzbekistan. The study explores the theoretical foundations of the sustainable development concept, as well as contemporary approaches to the formation of a green economy, energy efficiency, and rational use of natural resources. Particular attention is paid to the analysis of the state policy of the Republic of Uzbekistan in the field of economic greening, including regulatory and legal frameworks, sustainable development strategies, and programs for the transition to a green economy.
Keywords: sustainable development; environmental sustainability; economic efficiency; green economy; energy efficiency; water conservation; economy of Uzbekistan